1997
DOI: 10.1111/j.1365-2044.1997.258-az0396.x
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic nerve palsy following uneventful sciatic nerve block

Abstract: SummaryWe describe the loss of function in the sciatic nerve after an uneventful sciatic nerve block using 25 ml of lignocaine 1% with adrenaline 1 in 200 000 in a patient receiving b blocker drugs. Lack of pain on injection and complete regeneration of the nerve after 12 months in a patient with severe peripheral vascular disease led us to postulate ischaemic nerve damage as a mechanism of injury. Adrenaline-induced unopposed a-mediated vasoconstriction in a b-blocked patient is suggested as a possible mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However, there are reports with what seem to be direct nerve injections in patients who were lightly sedated, or not sedated at all, and the patients did not report any pain in the course of the local anesthetic injection 1114. Absence of an acute reaction in injected individuals may prevent them from seeking help immediately and lead to development of later consequences.…”
mentioning
confidence: 97%
“…However, there are reports with what seem to be direct nerve injections in patients who were lightly sedated, or not sedated at all, and the patients did not report any pain in the course of the local anesthetic injection 1114. Absence of an acute reaction in injected individuals may prevent them from seeking help immediately and lead to development of later consequences.…”
mentioning
confidence: 97%
“…However, considerable evidence suggested that nerve injury may occur even in the absence of pain on injection, making this symptom unreliable. [14][15][16][17] One study performed in small animals suggests that intraneural injection may be associated with high initial injection pressure. 18 However, the relationship between injection pressure and intraneural injection, and subsequent neurologic consequences, remains unclear.…”
mentioning
confidence: 99%
“…We also instructed the patient to report the occurrence of paresthesia during the injection process. There is documentation of nerve damage occurring after an uneventful nerve block [12]. However, in the latter case, postoperative sciatic nerve palsy was not caused by direct trauma from the needle.…”
Section: Discussionmentioning
confidence: 86%